2014
DOI: 10.5114/pm.2014.46471
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D insufficiency in community-dwelling postmenopausal Polish women

Abstract: IntroductionInadequate vitamin D level is associated with altered bone turnover and bone loss, which increases the fracture risk.AimTo assess the seasonal prevalence of inadequate (insufficient or deficient) serum vitamin D levels in community-dwelling postmenopausal Polish women screened for osteoporosis.Material and methodsA cross-sectional observational study based on the regional urban non-institutionalized sample (n = 107) of postmenopausal Caucasian women in the age range of 51-83 years, not taking any m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
7
1
3
Order By: Relevance
“…Vitamin D 3 , whose active form 1,25(OH) 2 D 3 is a cofactor required for calcium absorption in the gastrointestinal tract, is also strongly correlated with bone density [ 59 ]. Vitamin D insufficiency (25(OH)D 3 serum levels <50 nmol/L) is also not uncommon due to diet, lack of sun exposure, or genetic mutations [ 60 ], and many studies have shown that the majority of postmenopausal women in areas around the world have insufficient vitamin D levels [ 61 , 62 , 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…Vitamin D 3 , whose active form 1,25(OH) 2 D 3 is a cofactor required for calcium absorption in the gastrointestinal tract, is also strongly correlated with bone density [ 59 ]. Vitamin D insufficiency (25(OH)D 3 serum levels <50 nmol/L) is also not uncommon due to diet, lack of sun exposure, or genetic mutations [ 60 ], and many studies have shown that the majority of postmenopausal women in areas around the world have insufficient vitamin D levels [ 61 , 62 , 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…W piśmiennictwie znajdują się prace, w których autorzy opisują zmiany w stężeniu witaminy D w zależności od pory roku, jednak uzyskane przez nich wyniki nie są jednoznaczne. Część badaczy wykazywała istotne różnice w stężeniu 25(OH)D w zależności od pory roku, przy czym większe stężenie 25(OH)D w osoczu i rzadsze występowanie deficytowego jej stężenia stwierdzano w okresie wiosenno-letnim [26][27][28]. Inni uczeni uzyskali wyniki niepotwierdzające tej zależności.…”
Section: Omówienieunclassified
“…5 In addition to the limited oral intake and age-related decline in its absorption, decreased exposure to sunlight is among the leading causes of VitD insufficiency in women. 6 Agerelated changes that contribute to the reduced serum levels of this vitamin are mediated through the attenuation of hypodermal synthesis of VitD precursor, as well as reductions in alimentary absorption of cholesterol-based provitamin molecules in daily nutritional intake. 7 VitD insufficiency has been implicated in increasing prevalence of autoimmune diseases, including type I diabetes mellitus, 8 rheumatoid arthritis 9 and systemic lupus erythematosus.…”
Section: Introductionmentioning
confidence: 99%